2002
DOI: 10.2307/3078914
|View full text |Cite
|
Sign up to set email alerts
|

Species Richness, Environmental Correlates, and Spatial Scale: A Test Using South African Birds

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 19 publications
8
74
0
Order By: Relevance
“…This is in accord with the findings of Van Rensburg et al (2002), and those of similar studies of several other assemblages (Waide et al 1999;Mittelbach et al 2001). Within South Africa, the monotonic increase of avian species richness with energy at a quarter-degree resolution is not a by-product of more productive areas having a greater geographical extent (cf.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This is in accord with the findings of Van Rensburg et al (2002), and those of similar studies of several other assemblages (Waide et al 1999;Mittelbach et al 2001). Within South Africa, the monotonic increase of avian species richness with energy at a quarter-degree resolution is not a by-product of more productive areas having a greater geographical extent (cf.…”
Section: Discussionsupporting
confidence: 81%
“…Measures of NDVI were used as measures of energy because they were available at a finer resolution than the half-degree NDVI 0 0.62 measures of net primary productivity (NPP) (Woodward et al 2001) that have previously been employed in documenting a species-energy relationship for the South African avifauna (Van Rensburg et al 2002). However, at a half-degree resolution the two are closely correlated (r 2 = 0.81, p Ͻ 0.001).…”
Section: (A) Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The few studies that have looked into this issue report that when correlations are found these are usually weak and vary in strength with the scale of analysis (Gaston 1996, Bokma et al 2001, Jetz & Rahbek 2001, van Rensburg et al 2002. Covariation has been explained by a shared latitudinal effect (Pearson & Cassola 1992, Flather et al 1997, however, since latitude per se does not affect species richness, the pattern remains largely unexplained.…”
Section: Introductionmentioning
confidence: 99%